Comprehensive Assessment Of Post Surgical Complication Related Successes In Patients Treated With Prefabricated And Custom Made Abutments At Different Timings: An Original Research Study (Journal of Pharmaceutical Negative Results, 2023)
Background & Aim: Implant treatment is well accepted as prosthetic substitution option for different clinical circumstances. Nevertheless, clinical complications are also highly common with these therapies. This study was conducted to comprehensively assess the post surgical complication related successes in patients treated with prefabricated and custom made abutments at different timings.Materials and Methods: Total 30 patients were included for complication based success rate of implant therapy. Patients were divided in to two study groups of 15 each based on the type of abutment used over them. Group 1 consisted of patient who received Prefabricated implant Abutments. Group 2 consisted of patient who received custom made implant abutments. Implant success were checked at different timings 2 months, 4 months and 6 months. Patients with any post operative loss of follow up were excluded from the study. Data was sent for statistical analysis using SPSS software. P value less than 0.05 was taken as significant. Statistical Analysis & Results: Data analysis was done by SPSS software. All 30 subjects were studied with 18 male and 12 females in the age range of 40 to 60 years. In group 1, with increasing post operative follow up time, there was a clear decline in implant success rate. Also, in 6 months post operative time, the failure rate was highest. In group 2 also, there was a clear decline in implant success rate based upon the complications. P value was highly significant for 15 successful implants seen in 2 months post operative follow up time (with custom made abutments). Evaluation in the 2 study groups using one-way ANOVA showed significant p value (0.002).Conclusion: Authors concluded that there was an obvious rise in implant related complications with increasing post operative time. In the 6 months post operative follow up period, lowest success rate was seen in both of the studied groups (prefabricated abutments, custom made abutments). Authors also anticipate other long term similar studies with wider parameters and larger samples.